SOURCE PARAMETER DETERMINATION OF LOCAL EARTHQUAKE IN KOREA USING MOMENT TENSOR INVERSION OF SINGLE STATION DATA - Kim S.G.; Kraeva N. (My University, 1999)
The purpose of this investigation is to determine source parameters such as focal mechanism, seismic moment, moment magnitude, and source depth from recent small earthquakes in the Korean Peninsula using broadband records of three-component single station. It is very important and worthwhile to use a three-com-ponent single station in Korea because for most Korean earthquakes it is not possible to read enough first motions of P-wave arrivals because of the poor coverage of the seismic network and the small size (ML 5.0 or less) of the events. Furthermore the recent installation of the very broadband seismic stations in Korea and use of a 3D tomography technique can enhance moment tensor inversion to determine the source parameters of small earthquakes (ME 5.0 or less) that occur at near-regional distances (A -< 500 km). The focal solution for the Youngwol earthquake of 13 December 1996 is found to be a right-lateral strike slip event with a NE strike, and the Kyongju earthquake of 25 June 1997 is found to be an oblique reverse fault with a slight component of left-lateral slip in the SE direction.